2015
DOI: 10.1093/nar/gkv151
|View full text |Cite
|
Sign up to set email alerts
|

Base-resolution methylation patterns accurately predict transcription factor bindings in vivo

Abstract: Detecting in vivo transcription factor (TF) binding is important for understanding gene regulatory circuitries. ChIP-seq is a powerful technique to empirically define TF binding in vivo. However, the multitude of distinct TFs makes genome-wide profiling for them all labor-intensive and costly. Algorithms for in silico prediction of TF binding have been developed, based mostly on histone modification or DNase I hypersensitivity data in conjunction with DNA motif and other genomic features. However, technical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
(56 reference statements)
0
37
0
1
Order By: Relevance
“…The anticorrelation of mCG and TF binding is predictive in inferring TFBS (27) and enhancers (23,28). These observations led us to take advantage of mCG depletion as a high-resolution (∼1 bp depending on density of CG sites) enhancer signature that is complementary to the lower-resolution histone modification data derived from ChIPseq experiments (with fragment size ranging from 200 to 600 bp after sonication) (29).…”
Section: Significancementioning
confidence: 99%
“…The anticorrelation of mCG and TF binding is predictive in inferring TFBS (27) and enhancers (23,28). These observations led us to take advantage of mCG depletion as a high-resolution (∼1 bp depending on density of CG sites) enhancer signature that is complementary to the lower-resolution histone modification data derived from ChIPseq experiments (with fragment size ranging from 200 to 600 bp after sonication) (29).…”
Section: Significancementioning
confidence: 99%
“…However, for sequencing based DNA methylation profiling approach (BS-seq), the basic model assumption is completely different. Beta binomial model is widely used in analyzing BS-seq data (Feng et al 2014; Xu et al 2015). This paper mainly discusses the improvement of HM in array data, thus we only show one state-of-the-art beta binomial Bayesian hierarchical model (DSS) for differential methylated locus (DML) calling of BS-seq data (Feng et al 2014) and our stratified strategy (stDSS) to explore the possibility to borrow information across platforms.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the first principal component was able to predict a TF’s differential binding at its motif sites. Besides DH and HMs, Xu et al found that DNA methylation can also be used to predict TFBSs [55]. They found that DNA methylation levels around TFBSs and non-TF binding sites show distinct patterns.…”
Section: Applications Of Prediction Methodsmentioning
confidence: 99%
“…This is an example of a shape feature. Two other examples of shape features are a DNA methylation valley surrounding a TFBS [55] and a bimodal distribution of histone modifications due to nucleosome displacement for TFBS prediction [80]. …”
Section: Analytical Challenges and Solutionsmentioning
confidence: 99%